NIKAH MISYAR DAN TERPENUHINYA HAK DAN KEWAJIBAN SUAMI ISTRI - Hermanto, Agus; Wulandari, Dwi; Meriyati, Meriyati (Universitas Islam Negeri Raden Intan Lampung, 2020)
Misyar marriage is a marriage in which a wife is willing to give up part of her rights and live separately from her husband. The scholars' differed in their opinion regarding the law of performing misyar, but what is more important to discuss is how the concept of rights and obligations of husband and wife can be achieved. The purpose of this study is to analyze the couple’s rights concept and obligations in misyar. Through a qualitative literature review, this study examines the validity of misyar according to the scholars and the fulfillment of the rights and obligations of husband and wife using an interdisciplinary approach. Misyar is still said to be valid if the conditions and harmonious marriage are fulfilled, as for the cancellation of some of the rights required or permitted by one of the partners does not make this marriage haram, but some scholars call it makruh and even prohibit it, because it will bring harm to the wife and not fulfill the rights and obligations. Misyar seems as if the goal is only to fulfill lust and forget the main purpose of marriage which is essential to achieve a safe family.